Can Local Farms Survive Globalization?. (August 2014) - Arita, Shawn; Hemanchandra, Dilini; Leung, PingSun
Abstract : Due to expanding trade and increasing concentration of production during the past few decades, small local farms have faced ever-growing competitive pressures. We investigate the impacts of this globalization on production of local food by examining Hawai'i's open island economy and econometrically evaluating impacts of import competition on the growth and survival of individual fruit and vegetable farms. We find evidence that rising levels of imports significantly hinder farm growth in Hawai'i and have a smaller impact on farm survival. Increased foreign competition increases the likelihood of exit for commercial farms but has little effect on small noncommercial farms.